Combined Supplementation of Choline and Docosahexaenoic Acid during Pregnancy Enhances Neurodevelopment of Fetal Hippocampus - Huban Thomas Rajarethnem; Kumar Megur Ramakrishna Bhat; Malsawmzuali Jc; Siva Kumar Gopalkrishnan; Ramesh Babu Mugundhu Gopalram; Kiranmai Sesappa Rai (Neurology Research International)
Choline is an essential nutrient for humans which plays an important role in structural integrity and signaling functions. Docosahexaenoic acid (DHA) is a polyunsaturated fatty acid, highly enriched in cell membranes of the brain. Dietary intake of choline or DHA alone by pregnant mothers directly affects fetal brain development and function. But no studies show the efficacy of combined supplementation of choline and DHA on fetal neurodevelopment. The aim of the present study was to analyze fetal neurodevelopment on combined supplementation of pregnant dams with choline and DHA. Pregnant dams were divided into five groups: normal control [NC], saline control [SC], choline [C], DHA, and C + DHA. Saline, choline, and DHA were given as supplements to appropriate groups of dams. NC dams were undisturbed during entire gestation. On postnatal day (PND) 40, brains were processed for Cresyl staining. Pups from choline or DHA supplemented group showed significant (p<0.05) increase in number of neurons in hippocampus when compared to the same in NC and SC groups. Moreover, pups from C + DHA supplemented group showed significantly higher number of neurons (p<0.001) in hippocampus when compared to the same in NC and SC groups. Thus combined supplementation of choline and DHA during normal pregnancy enhances fetal hippocampal neurodevelopment better than supplementation of choline or DHA alone.